The neuroendocrine response to stress under the effect of drugs: Negative synergy between amphetamine and stressors. (January 2016) - Gómez-Román, Almudena; Ortega-Sánchez, Juan A.; Rotllant, David; Gagliano, Humberto; Belda, Xavier; Delgado-Morales, Raúl; Marín-Blasco, Ignacio; Nadal, Roser; Armario, Antonio
Highlights: Amphetamine reduces hypothalamic-pituitary-adrenal response to stress. Amphetamine blocks stress-induced hyperglycemia. Amphetamine reduces stress-induced c-fos expression in the PVN. Amphetamine blocks stress-induced CRH gene expression. Abstract: There have been numerous studies into the interaction between stress and addictive drugs, yet few have specifically addressed how the organism responds to stress when under the influence of psychostimulants. Thus, we studied the effects of different acute stressors (immobilization, interleukin-1β and forced swimming) in young adult male rats simultaneously exposed to amphetamine (AMPH, 4 mg/kg SC), evaluating classic biological markers. AMPH administration itself augmented the plasma hypothalamic-pituitary-adrenal (HPA) hormones, adrenocorticotropin (ACTH) and corticosterone, without affecting plasma glucose levels. By contrast, this drug dampened the peripheral HPA axis, as well as the response of glucose to the three stressors. We also found that AMPH administration completely blocked the forced swim-induced expression of the corticotropin-releasing hormone (hnCRH) and it partially reduced c-fos expression in the paraventricular nucleus of the hypothalamus (PVN). Indeed, this negative synergy in the forced swim test could even be observed with a lower dose of AMPH (1 mg/kg, SC), a dose that is usually received in self-administration experiments. In conclusion, when rats that receive AMPH are subjected to stress, a negative synergy occurs that dampens the prototypic peripheral physiological response to stress and activation of the PVN.